Understanding Barriers to Doing Business : Survey Results of How the Justice System Impacts the Business Climate in South East Europe - World Bank Group (World Bank, Washington, DC, 2019)
This report documents the results of a survey that was conducted to better understand howthe justice system affects the business environment in eight countries in South East Europe (SEE);Albania, Bosnia and Herzegovina, Bulgaria, Croatia, Kosovo, Montenegro, North Macedonia andSerbia. The primary purpose of the Survey was to analyze businesses’ perceptions of and experienceswith the justice system and in particular, the performance of the courts in their respective countries. The Survey also identified the challenges businesses face in their daily operations, assessed the impact of the justice system on businesses and established which justice issues present the greatest obstacles for business operations and growth. This research is part of a broader initiative to inform justice policy dialogue and reform in the Western Balkans.